El garantismo y el punitivismo en el Código Orgánico Integral Penal - Sebastián Cornejo Aguiar (Universidad Hemisferios, 2016)
The objective of this article is to determine the need for the existence of a punitive and a guarantor party within the Integrated Criminal Code, starting from the study of the doctrinal updating in criminal matters within the Ecuadorian legal system considering that since Ecuador is a constitutional State Of rights and justice, inspires us to construct mechanisms that have as basis and aim the protection of the freedoms of the individual, against the various forms of the arbitrary exercise of punitive power of the State, where the guarantees and principles established in the Code Organic Integral Criminal, should be considered as punitive power containment filters that prevent that power from overflowing and destroying everything in its path. Then the meaning of the guarantee and punitivity is analyzed. Finally, we consider the relationship between guarantee and punitivity, concluding that the guaranty is a current that provides substantial ideas to transform the judicial process thus preventing the arbitrariness of punitive power.